Otimização da Produção de Enzimas por Aspergillus niger em Fermentação em Estado Sólido - Rocha, Christiane Pereira (2010)
Brazil is one of the main producer countries of rice and passion fruit. The production of these foods have generated a large amount of wastes which could represent serious problems with the final disposal and cause economic losses from misuse of biomass. The enviroment pollution and loss of economic value from this biomass can be reduced by using this material in the production of enzymes by solid state fermentation (SSF).This reduction of waste generation fit neatly into the conceptual framework of by-products utilization, waste minimization and waste prevention which have been accepted as part of the environmental and economic interaction in the food supply chain. For this reason, the present work has, as objective, to evaluate the production of the enzymes invertase, amylase, cellulase, pectinase, and proteinase using Aspergillus niger in solid state fermentation (SSF) on rice and passion fruit by-products. In order to choose a strain and optimize the fermentation conditions the production of these enzymes using Aspergillus niger strains ATCC 16404, 1057 and 9029 were preliminary evaluated and the fermentation with the best strain was investigated. According to the results obtained, the best strain for all five enzymes were Aspergillus niger ATCC 16404 and four days was found to be the best time for the fermentation. Central composite design (CCD) was used to investigate the dependence of solid medium concentrations (SMC), water addition (WA) and inoculum size (IS) on the production of enzymes during the SSF. The variable levels used in the design were: 0 to 1.0 g rice by-product/ total g, 0.323 to 1.676 mL/ total g , and 0.5 a 4.5 mg inoculum/ total g . According to the results the variable levels used in CCD was satisfactory to describe the optimization. Based on response surface methodology (RSM), optimum conditions were: SMC 0.5 g rice by-product/ total g, WA 1.0 mL/ total g, , IS 2.5 mg/ total g, invertase 108.82 ± 3.1 U/total g , amylase 10.56 ± 2.0 U/ total g , cellulase 5.98 ± 0.8 U/g , pectinase 5.24 ± 0.6 U/g, and proteinase 5201.00 ± 3.8 U/g. To obtain a structured model that describe the nonisothermal cellular behaviour and to evaluate the kinetics of cell growth and enzyme production a new set of experiments were carried out at the temperatures of 28 ± 2ºC, 35 ± 0.5ºC, 40 ± 0.5ºC e 45 ± 0.5ºC under the same optimum conditions described above. The results and model predictions implied that the largest cellular growth, expressed in terms of biomass and spores, occured in the medium with temperature between 35°C and 45ºC. The experimental results showed that the maximum enzymes activities and conditions related to this production were: invertase (155.80 ± 3.28 U/g) , 35ºC , 11 days of fermentation; amylase (14.00 ± 2.42 U/g) and proteinase (5809.00 ± 4.20 U/g), 28ºC, and 11 days of fermentation; cellulase (14.10 ± 2.25 U/g) and pectinase (10.80 ± 1.5 U/g), 45ºC, 12 days of fermentation. The comparisons between the activation energy of enzyme desactivation provided by model with published values and the comparison of model predictions with experimental results of cellular growth and enzyme activity demonstrate the applicability of the proposed model.